2022
DOI: 10.1111/nmo.14450
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Simo decoction on gastric motility of diabetic rats

Abstract: Gastroparesis is an extremely common condition among diabetic patients. The upper gastrointestinal symptoms of gastroparesis, such as early satiety and postprandial fullness, are associated with delayed gastric emptying. 1 Previous evidence has revealed that reduced antral contractions and increased postprandial antral diameter are responsible for delayed gastric emptying. 2 Although the pathophysiological mechanism of gastroparesis has not been fully elucidated, the etiology of this disorder is noted as follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In addition, the therapy aimed at regulating brain‐gut neurotransmitter has been effective in delayed gastric emptying 48 . Many TCM prescriptions have obvious effects in this respect and were gradually receiving attention 49,50 . The search for brain‐gut neurotransmitters from endogenous substances for the treatment of gastroparesis is maybe promising.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the therapy aimed at regulating brain‐gut neurotransmitter has been effective in delayed gastric emptying 48 . Many TCM prescriptions have obvious effects in this respect and were gradually receiving attention 49,50 . The search for brain‐gut neurotransmitters from endogenous substances for the treatment of gastroparesis is maybe promising.…”
Section: Discussionmentioning
confidence: 99%
“…48 Many TCM prescriptions have obvious effects in this respect and were gradually receiving attention. 49,50 The search for brain-gut neurotransmitters from endogenous substances for the treatment of gastroparesis is maybe promising.…”
Section: Current Options For Clinical Pharmacotherapy Of Gastroparesismentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of traditional Chinese patent medicine (TCPM), Simo decoction (Simo decoction oral solution) is distinguished by its effectiveness in treating various symptoms, including vomiting, abdominal bloating, abdominal pain, constipation, and feeding intolerance in premature infants, as well as constipation and functional dyspepsia in older adults [ [16] , [17] , [18] , [19] ]. A key component of this decoction is Arecae semen , traditionally used for its properties in eliminating intestinal parasites, alleviating food stagnation, stimulating qi, promoting diuresis, and preventing malaria [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of these drugs can enhance the immunity, invigorate the spleen and replenish Qi . Furthermore, it is found that SMD can restore and improve gastrointestinal motility by promoting gastric emptying and regulating hormones related to gastrointestinal motility ( Li et al, 2020 ; Yan et al, 2022 ). SMD could also treat constipation by improving the transcription level of genetic information of intestinal microbiota, increasing tyrosine-protein kinase growth factor receptors, and protecting the intestinal mucosal barrier ( Dai et al, 2013 ; He et al, 2017 ; Fan et al, 2018 ; Hui et al, 2018 ; Xiao and Liu, 2018 ).…”
Section: Introductionmentioning
confidence: 99%